State Financial Sources Versus Private Financial Sources: A Comparative Analysis of Funding of Public and Business Organizations in Indonesia - Ramdhani, Alika Cahya; Saepudin, Eli Apud; Oktaviani, Via; Magfiroh,; Mustika Dewi, Salsabila; Ramadila Sandy, Masri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Funding is a crucial aspect for the smooth operation of organizations, both public and business. In Indonesia, there are significant differences in the structure and sources of funding of these two types of organizations. This study aims to analyze and compare the funding of public and business organizations in Indonesia. Public and business organizations in Indonesia have an important role in national development. Both types of organizations require funding to run their operations and achieve their goals. This paper aims to analyze and compare the funding of public and business organizations in Indonesia. This research uses a descriptive method with a literature study. Data was collected from various sources such as books, journals, articles, and official websites of organizations. The results show that there are some significant differences in the funding of public and business organizations in Indonesia. The main funding source of public organizations is tax, while business organizations get funding from various sources such as own capital, bank loans, and capital markets. The use of public organizations' funds is regulated by laws and regulations, while business organizations have more flexibility in using their funds. This paper also discusses the challenges and opportunities of funding public and business organizations in Indonesia. This research is expected to contribute to the development of policies and strategies for funding public and business organizations in Indonesia.